The glosses of the Murbach Hymns. A study on syntax and language use in Old High German - Morawetz, L (2023)
The aim of this study is to systematically determine the linguistic and visual structures that constitute how Old High German glosses transmit information about linguistic features of the vernacular. Vernacular glosses are a unique linguistic phenomenon as they link between the main written language of the Middle Ages, Latin, and the mostly spoken Old High German. Since I argue that the pragmatic nature of glosses requires also an analysis of their material context, I developed a model that combines historical linguistics and manuscript studies, i.e. a functional net consisting of three interacting levels. Firstly, glosses are vertically related to their Latin lemma which they translate. Secondly, they are horizontally linked to each other in syntactic structures. Thirdly, they were written in a way that visually expresses linguistic features. I analysed the Murbach Hymns (MS. Junius 25, Oxford, Bodleian Library), a ninth-century interlinear version, in order to illustrate the characteristics of the functional net. Their glosses have been the subject of numerous studies regarding their cultural background and vocabulary but their significance for further areas of linguistic research has been doubted since they closely follow the Latin text. My analysis shows that the glosses were consistently based on the vernacular within the limitations of the main text. They provide valuable insights into Old High German linguistics. The three levels interact with each other, demonstrating incipient writing conventions and an intuitive implementation of linguistic knowledge. Taking into account the codicological context and history of the Murbach Hymns, my study determined that their glosses were an elaborate teaching aid designed to illustrate how the linguistic systems of Latin and Old High German function.